ANALISIS INDEKS KUALITAS AIR LINGKUNGAN PERTAMBANGAN BATUBARA PT KPC SUBDAS SANGATTA KALIMANTAN TIMUR - Komarawidjaja, Wage (Jurnal Teknologi Lingkungan, 2011)
Water quality index (IKA) is one tool to quickly predict the environmental quality statusÃ‚Â of an ecosystem or region to obtaining an alternative of the future management. Toanalyze the status of these indices utilize only data of environmental parameters thatÃ‚Â have been established as a key parameter determining the IKA.Ã‚Â From the analysis of the mining area of PT KPC IKA with key parameters TDS, DO,Ã‚Â COD, nitrogen (N) and phosphorus. (P) derived from the water quality of agriculturalÃ‚Â ecosystems, industry / mines and residential showed an index value of less well with thecategory (54.6163) on the interval 40 Ã¢â€°Â¤ IKA <60. The low index value is proportional toÃ‚Â the low value of ecosystem quality index industry / mining IKA (I) with a value of 45.82with categories of less well on the interval 40 Ã¢â€°Â¤ IKA <60. Consider, that the index valueÃ‚Â of ecosystem quality residential IKA (H) and agricultural ecosystem quality index IKAÃ‚Â (P) with good and excellent categories, then the ecosystem of industry / mining is theÃ‚Â focus that needs to be considered for improved management efforts.Ã‚Â